Čech systems and approximate inverse systems - Matijević, Vlasta (Array, 2020)
We generalize a result of the first author who proved that the Čech system of open covers of a Hausdorff arc-like space cannot induce an approximate system of the nerves of these covers under any choices of the meshes and the projections.